Antibacterial potency of garlic extract against certain skin pathogenic bacteria - Abdullahi M. Daskum; Kura M. Abdulrahim; Abubakar M. Dadile; Hajja Amma (Novel Research in Microbiology Journal)
The antibacterial potency of garlic extract (Allium sativum) against gram positive and gram negative skin pathogenic bacteria including; Staphylococcus aureus, Staphylococcus epidermidis, Streptococcus pyogenes, and Pseudomonas aeruginosa were studied using agar well diffusion and broth dilution assays. Agar well diffusion assay for aqueous garlic extract (AGE) was characterized with zones of inhibition ranging from 4.40 – 3.80cm, 4.13 - 3.57cm, 3.40 – 2.67cm for S. aureus, S. epidermidis and Strep. pyogenes, respectively, however, Ps. aeruginosa had lesser zone of inhibition ranging from 2.32 – 1.55cm. Studying the antibacterial potency of AGE against the selected isolates, revealed that it is affected by temperature of storage. Current results showed that storage of AGE at low temperature of - 20oC, does not affect its potency, however, its potency was slightly lost at high temperatures above 37oC. The broth dilution test was performed to investigate the Minimum inhibitory concentration (MIC) and Minimum bactericidal concentration (MBC) of the AGE against the bacterial isolates at 37oC. Investigating the activity of AGE loaded on Gel dressing revealed that it can have potency when applied on patients with Staphylococcal skin infections. Findings from this study encourage and support the use of AGE in treating bacterial skin infections especially in developing countries like Africa, as it is available, economic and have no side effects.